The Implementation of Innovative Learning Models and English Teachers’ Challenges at Man 2 POSO (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to find out what kind of Innovative Learning Models that used by the teachers, the ways teachers implemented Innovative Learning Models in class, and the challenges faced by the teachers. This research used Qualitative Method Design. The data were obtained by using three instruments, which were interview, classroom observation checklist, and an interview guide. The subjects of this research were three English teachers who taught the tenth, eleventh and twelfth grades selected by Purposive Sampling Technique The findings of this research revealed that the three teachers implemented different Innovative Learning Models in class, namely Discovery Learning, Problem-based Learning and Project-based Learning. The implementation of innovative learning models were; (1) Discovery Learning Model, the steps were the teacher selects several materials, explained it then make students discover and investigate of the problem, by themselves. (2) Problem-based Learning, the teacher explained the material, students were asked to find out the problems, students then presented the result, and students will provide a reflection, as a result of the investigation. (3) Project-based Learning, the steps are the teacher gives students a project related to the material, then assesses it as an output of the learning and evaluates it. The teachers mainly introduced technology features of the internet to collect the assignment given. Related to challenges, the three teachers faced challenges in managing their time in implementing learning models, enhancing the students’ motivation to learn English as a language, and the difficulties of students using technology.